Clinical Pharmacological Approach To The Use Of Antibacterial Therapy In Older People - Rasulov B.A. (Zien Journals, 2025)
The clinical pharmacological approach to antibacterial therapy in older people is crucial for ensuring effective treatment while minimizing adverse effects and resistance development. This article explores age-related physiological changes that influence drug pharmacokinetics and pharmacodynamics, including altered absorption, distribution, metabolism, and excretion. The selection of appropriate antibacterial agents, dose adjustments, drug interactions, and the risks of polypharmacy in elderly patients are analyzed. Additionally, strategies for optimizing therapy to reduce antibiotic resistance and improve patient outcomes are discussed, along with recent advancements in geriatric antimicrobial stewardship
Keywords: Antibacterial therapy; elderly patients